In the streets and bazaars of Harbin: marketers, small traders, and peddlers in a changing multicultural City - Grüner, Frank (Itinerario, 2011)
The Zelenyi [Green] Bazaar is like a self-contained village, where each house is a small shop. The Chinese traded and lived here. They represented ninety percent [of the bazaar population]; the rest of the territory was inhabited by the poorer Russian emigrants, who were only able to buy small, cheap houses and only lived in these, without trading in them. At the other ends of the city these people were referred to as the Zelenobazarskie [the people from Zelenyi Bazaar], which was not exactly a compliment. The small house-shops were closely packed together—God forbid a fire was to break out—when this happened, the flames were carried from house to house with unbelievable speed and destroyed the wooden constructions. And when it had rained, the ground was thick with mud. The bazaar itself was abundant with all possible products, with meat and fish as well as many kinds of textiles. There were two or three photographic studios and even several small tailors. The bazaar was generally seen as the place where it was practical to have a look at all possible goods.
Published online: 14 March 2012
Gesehen am 18.07.2022